Biotische und landschaftliche Diversität in autochthonen Agroforstsystemen.: Eine Fallstudie aus Westkenia - Backes, Martina M. (ERDKUNDE, 1998)
Autochthonous agroforestry systems have mainly evolved in former natural forest areas or tree-rich vegetation formations, such as woodlands. In such agroecosystems a high degree of diversity of indigenous tree species (-diversity) must be expected. Knowledge about the contribution of agroforestry land-use to the in-situ conservation of biotic diversity is scarce. This case study on the diversity of indigenous woody perennials in tree-based land-use forms of the Bukusu agroforestry system in Western Kenya is exemplary for East African smallholder farming systems. Those vegetation formations of medium to low human disturbance intensity and linked with autochthonous land-use strategies are rich in floristic make-up, speaking for a high conservation value. As regards floristic diversity at a landscape scale, the frequency and constancy of diverse vegetation formations and tree-rich land management units are crucial for successful preservation of a high -diverisity of woody species. Botanical data are being related to findings obtained from retrospective land-use analysis. The results show clearly how spatial and functional heterogeneity of the land-use system does not simply portray ecological aspects. Rather, the cultural landscape diversity pattern reflects agrarian development and socio-economic circumstances from a historical perspective. The vegetation cover is being moulded by culture-specific decisions of the Bukusu people living and acting within the area studied. The species composition of complex vegetation structures, as the mosaic-like distribution of these functional units, are the result of interactions between naturally and culturally related factors. Interestingly enough, the most structurally diverse land-use forms with high -diversity values for woody species appear in areas with high population densities and a decrease in farm size, provided agricultural intensification followed progressive diversification of traditional land-use by taking up autochthonous components. The structural order of the anthropogenetically differentiated vegetation cover reflects complex interactions of a set of complementary functions and interrelated land-use strategies of agroecological, socio-cultural and economic kinds of factor. The flexibility of the eminently differentiated land-use system is on the basis of biological and economic buffer capacities due to tree species richness, in turn facilitating integral and dynamic functioning of the land use system in its entirety.